PENINGKATAN KEMAMPUAN SISWA DALAM MEMECAHKAN MASALAH SOSIOLOGI MELALUI MODEL PBL DENGAN PENDEKATAN KONTEKSTUAL - Prasetyaningrum, Uniek; Supriadi, Supriadi; Imran, Imran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract The research’s title is Improving Students’ Competence in Solving Sociological Problems through Problem Based Learning using Contextual Approach. It is assumed that teaching sociology subject in the school has not yet made the students critical to think. Besides, there are still limited teaching methodology used in the class resulting in low participation of students’ activity in group work discussion. This action research using contextual approach was participated by students of class X-G consisting of 11 male students and 23 female students and a sociology teacher. Data was collected by using observation, discussion sheet, and documentation. This study proposed two cycles; first cycle consisted of two meetings and the second cycle was three meetings. The research finding showed that average score of students before this research was still low, only 8 students passed minimal competence. However, after the first cycle was completed, it can be seen that students’competence in solving sociological problems improved well, around 14 students actively participated in the discussion. After cycle II was finished, the students’ competence sharly increased and 31 students were active participating in group work discussion. Keywords : Problem-Based Learning, Contextual Approach, Classroom Action Research, Students’ Competence in Solving Sociological Problems